2011
DOI: 10.1128/jvi.01515-10
|View full text |Cite
|
Sign up to set email alerts
|

The C-Terminal nsP1a Protein of Human Astrovirus Is a Phosphoprotein That Interacts with the Viral Polymerase

Abstract: Human astrovirus nonstructural C-terminal nsP1a protein (nsP1a/4) colocalizes with the endoplasmic reticulum and viral RNA. It has been suggested that nsP1a/4 protein is involved in the RNA replication process in endoplasmic reticulum-derived intracellular membranes. A hypervariable region (HVR) is contained in the nsP1a/4 protein, and different replicative patterns can be distinguished depending on its variability. In the present work, both the astrovirus RNA-dependent RNA polymerase and four types (IV, V, VI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…Nsp1a/4 interacts with the RNA polymerase when translated in vitro, and this interaction depends on the phosphorylation status of the protein. The fact that the proposed phosphorylation site is in the putative VPg region supports the idea that nsp1a/4 could be implicated in the replication of the astrovirus genome [ 20 ] . In addition, nsp1a/4 has a perinuclear distribution near the endoplasmic reticulum and colocalizes with viral RNA [ 29 ] .…”
Section: General Features Of Nonstructural Proteinsmentioning
confidence: 79%
See 1 more Smart Citation
“…Nsp1a/4 interacts with the RNA polymerase when translated in vitro, and this interaction depends on the phosphorylation status of the protein. The fact that the proposed phosphorylation site is in the putative VPg region supports the idea that nsp1a/4 could be implicated in the replication of the astrovirus genome [ 20 ] . In addition, nsp1a/4 has a perinuclear distribution near the endoplasmic reticulum and colocalizes with viral RNA [ 29 ] .…”
Section: General Features Of Nonstructural Proteinsmentioning
confidence: 79%
“…However, conclusions drawn from these reports suggest that at least fi ve nonstructural proteins exist (Fig. 2.3 ) (1) an N-terminal 20-kDa protein, likely cleaved co-translationally by a cellular signalase that contains one predicted transmembrane domain and a coiledcoil domain [ 56 ] ; (2) a protein predicted to contain four transmembrane domains, although a protein from this hydrophobic region of nsp1a has not been identi fi ed; (3) a 27-kDa serine protease [ 22,37 ] ; (4) a phosphoprotein of 21-27 kDa depending on its level of phosphorylation or differential processing that contains the hypervariable nsp1a region and possibly is the VPg protein [ 2,20,29 ] ; and (5) a 57-kDa RNA-dependent RNA polymerase [ 22,43 ] . Finally, two reported small products of 5.5 and 6.5 kDa have not been mapped in nsp1a [ 74 ] .…”
Section: Nonstructural Polyprotein Synthesis and Processingmentioning
confidence: 99%
“…Alternatively, it could also be due to posttranslational modifications of the protein, such as phosphorylation. In fact, the C-terminal nsP1a protein expressed in insect cells is modified posttranslationally by phosphorylation (10), and although phosphorylated residues were not specifically identified, some of the potential phosphorylation sites are located within the putative VPg region, specifically the Tyr at positions 693, 728, 729 and 747 (17). Indeed, phosphorylation has been described as a posttranslational modification of sobemo-and potyviral VPgs (37,40).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, phosphorylation has been described as a posttranslational modification of sobemo-and potyviral VPgs (37,40). Moreover, the C-terminal nsP1a protein interacts with itself to form oligomers and with the viral RdRp (10). Interest- ingly, the oligomerization and polymerase interaction domains map between residues 744 and 777 and residues 655 and 743 of nsP1a polyprotein (10), respectively, which lie partially in the first case and almost completely in the second case in the putative VPg region (amino acids 665 to 755).…”
Section: Discussionmentioning
confidence: 99%
“…Several putative transmembrane domains that could help in driving and anchoring the nonstructural replication complexes on cellular membranes have been identified in the nsP1a polyproteins (13,62 (75,77,78,80). It has been shown that some of the resulting nonstructural proteins are posttranslationally modified by phosphorylation mechanisms (81,82), and these modifications may modulate the interaction among them. Whether the proteolytic processing of these nonstructural polyproteins takes place before or after anchoring to intracellular membranes is still unknown, but large membrane rearrangements are observed in HAstV-infected cells both in vitro (82,83) and in vivo (84).…”
Section: Translation/replicationmentioning
confidence: 99%